Secrets of the sideshows - Nickell, Joe (University Press of Kentucky, 2005)
On small-town ballfields and county fairgrounds, the sideshow performers set up their tents and trailers in the shadow of the Ferris wheel. There they amazed us with daring feats such as fire eating and sword swallowing, intrigued us with exhibitions of human oddities and various "anatomical wonders," and yes, deceived us with illusions such as "Atasha the Gorilla Girl" and even outright fakes. These bizarre spectacles engaged the mind as well as the eye. Was the human blockhead act, in which the performer pounded a large nail or ice pick into his nostril, real or fake? Was the so-called allig